Realization of self-poled, high performance, flexible piezoelectric energy harvester by employing PDMS-rGO as sandwich layer between P(VDF-TrFE)-PMN-PT composite sheets. (15th February 2019) - Yaqoob, Usman; Habibur, Rahaman Md; Sheeraz, Muhammad; Kim, Hyeon Cheol
Abstract: This study investigates the role of highly charged uniform electrostatic polydimethylsiloxane-reduced graphene oxide (PDMS-rGO) layer in achieving the self-poled piezoelectric energy harvester (PEEH) using P(VDF-TrFE)-PMN-PT composite sheets. To obtain the tri-layer structure the PDMS-rGO layer was sandwiched between two P(VDF-TrFE)-PMN-PT composite sheets using spin coating technique. From the X-ray diffraction pattern it was projected that the highly charged PDMS-rGO layer attracts the dipoles from upper and lower P(VDF-TrFE)-PMN-PT sheets and then facilitates them in aligning in one direction without any external electric field. The output performances of the self-poled tri-layer energy harvester (EH) was observed using finger tapping (∼2.5 N), the maximum open circuit voltage and short circuit current was measured around 8.5 Vpk-pk and 3 μApk-pk, respectively. Furthermore, the as-fabricated self-poled tri-layer energy harvester (EH) reveals the maximum power density of 6.1 μW/cm [2]. Finally, in order to realize its implementation in realistic application, it was attached on the insole of a shoe and on a bicycle. The device reveals good mechanical flexibility and stability during several times walking and running. Finally, our highly flexible, self-poled piezoelectric energy harvester can be a potential candidate for its employment is various futuristic portable electronics. Graphical abstract: